Integrated Marketing and Customersâ€™ Decision Saving Funds in Islamic Banks - Wenda Wahyu Christiyanto; Mardi Astutik (Shirkah: Journal of Economics and Business, 2018)
Indonesia has a good market potential for Islamic banking business development. However, the market share of Islamic banks is still far behind the conventional ones. Over 5 years, Islamic marketing mix has been integrated with the contemporary marketing mix. This article prudently examines the decision of society to invest their funds in Islamic banks dealing with the integrated marketing mix. Questionnaires had been distributed to 150 respondents of Islamic banks customers. Using analysis of Structural Equation Modeling based on variance (SEM-PLS), this article shows that the integrated marketing mix has taken an influence on customer purchasing decisions, consisting of pragmatism and product, pertinence and promotion, persistence and process.Â Keywords: SEM-PLS, Islamic banking, integrated marketingÂ